FRANCHISING AS A MEANS OF ACHIEVING INTERNATIONALIZATION: RESEARCH PROPOSITIONS FROM A MULTIPLE CASE STUDY OF BRAZILIAN FASHION RETAILERS - Almeida, Victor Manoel Cunha de; Borini, Felipe Mendes; Silveira, Thiago Cruz; Avrichir, Ilan (Contextus - Revista Contemporânea de Economia e Gestão, 2015)
According to Brazilian Franchising Association, the number of Brazilian franchises has grown 300% in the last ten years, but only 3% of Brazilian franchises operate in foreign markets, so the opportunity to internationalization is strong. Aiming to get a better understanding of possible distinctive features of Brazilian retail internationalization, this paper explores the determinants of franchising as the choice of internationalization entry mode by Brazilian’s firms in the fashion apparel sector. The multiple-case study was the approach used. The study resulted in eleven research propositions. Results show that government or trade organizations support, geographic distance, political and economic risk may not be determinant to internationalization. However cultural proximity and relationship with local partners can be determinant to internationalization. Moreover, brands that cater to a very specific segment and that their value proposition is closely linked to intangible factors may face problems in expanding to culturally distant international environments.